The Design of the Information System of Web-Based Alumni Data Tracking - Sutedi Sutedi (Jurnal Ilmiah ESAI, 2012)
Alumni’s success in getting jobs that are suitable with their competence and with appropriate income soon after graduation is an indicator of success of a study program. Therefore, it is necessary to develop a system that can help track the alumni data easily. The development of the information system of web-based alumni data tracking can be an alternative solution taking into consideration that the alumni can report the development of their career wherever and whenever they would like to. However, for the purpose of the completeness of the alumni data, it is necessary to develop a variety of attributes to track alumni data more completely. Keywords:  alumni, attribute, web.